Factor affecting University students’ brand loyalty towards foreign brand beauty and skin care product - Nurul Nadia Ashikin, Japeri (2015)
It is normally argued that consumers become loyal to a particular brand based on their perception toward the brands itself. As a result, there is growing evidence that adopting a brand perception positively influences consumers‟ brand loyalty. To date, however, this research aims to investigate the relationship between brand consciousness with perceived quality, emotional value and brand involvement. In addition, this research also concentrated on the influence of three key variables which is perceived quality, emotional value and brand involvement on university students‟ brand loyalty toward foreign brand beauty and skin care product. A total of 318 students in UUM participated in the survey. Using multiple regression analysis, the study finds that brand consciousness is positively related to perceived quality and emotional value, but not to brand involvement of a foreign brand beauty and skin care product. Perceived quality and emotional value positively influence toward foreign beauty and skin care product, while brand involvement negatively influence brand loyalty. This study provides valuable implication for international or foreign marketer who plans to enter Malaysian market. Based on the finding, international or foreign marketer should focus on quality and emotional aspects of their brand in order to attract Malaysian consumers, especially for those who are brand conscious